Preschool Children and their Preconceptions of Nature in a Nursery School Setting - Pavla Krátká; Alena Srbená (University of Zadar, 2022)
The present paper focuses on preschool children's pre-literacy in natural science with an emphasis on their preconceptions of nature in the current conditions of nursery schools in the Czech Republic. The key objectives of the paper include the following: Examine how children interpret the term nature. The objective and focus of the paper are based on the assumption that if people understand the theory of a particular topic, they are also interested in its practical aspects. In the context of nature and its protection, this idea may be interpreted as follows: If we understand nature and its fundamental laws, we can protect it better. Nature and environmental protection is becoming increasingly relevant and must be supported from early childhood from a global perspective.